Association of High TPO Antibody Titer with Differentiated Thyroid Carcinoma: A Case-Control Study (Bangladesh Journal of Nuclear Medicine, 2023)
Background: The most common well-differentiated thyroid carcinomas are papillary thyroid carcinoma (PTC) and follicular thyroid carcinoma (FTC). PTC accounts for 80–90% of all thyroid cancers, and follicular carcinoma accounts for 10–15% of all thyroid cancers. Common established risk factors for thyroid carcinoma are head-neck irradiation, a positive family history, and a few genetic disorders. High anti-thyroglobulin antibodies (TgAb) have already been established as predictive markers for thyroid carcinoma, but anti-thyroid peroxidase antibodies (TPO Ab) have not been established as predictive markers till now.Objective: To find out the association of high TPO Ab titer with differentiated thyroid carcinoma (DTC).Patients and Methods: This case-control study was carried out at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Dhaka, from September 2020 to November 2021. A total of 52 cytologically diagnosed DTC patients who underwent thyroidectomy were selected as cases. Another 52 age- and sex-matched healthy individuals who had sonographically normal thyroid glands and a biochemically euthyroid state were selected as controls. The total number of participants was 104. Written informed consent was obtained from each of the participants. A detailed history was taken, and a thorough clinical examination was carried out on each patient. High resolution ultrasonography (HRUS) of the thyroid gland, serum thyroid-stimulating hormone (TSH) level, and fine needle aspiration cytology (FNAC) report of the thyroid nodule of each participant were collected. Serum TPO antibody levels were measured in patients with DTC prior to thyroid surgery, as well as in the control group, in the NINMAS laboratory using the CLIA method. After the collection of all the required data, analysis was done by SPSS 24.0.Results: The mean age of the cases was 35.8 ± 13.3 years and 34.6 ± 13.0 years in the control groups. Female patients were predominant in both the case and control groups (63.5% and 69.2%, respectively). Both groups were statistically almost similar in terms of age and sex. Around 46.2 % (n=24) patients in the case group had high serum TPO Ab levels and 15.4 % (n=8) of participants in the control group had high serum TPO Ab levels. The mean serum TPO Ab level in the case group was 306.77± 452.57 U/mL, and the mean serum TPO Ab level in the control group was 75.85±181.47 U/mL. Serum TPO antibody level was significantly higher in the case group compared to the control group (306.77±452.57 vs 75.85±181.47 U/mL, p = 0.001).Conclusion: There was a significant association of high TPO Ab titer found with DTCBangladesh J. Nuclear Med. 26(1): 34-38, 2023